2018
DOI: 10.1177/0954405418811783
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between wire feed speed and external mechanical constraint for enhanced process stability in underwater wet flux-cored arc welding

Abstract: It is a great challenge to improve the process stability in conventional underwater wet welding due to the formation of unstable bubble. In this study, mechanical constraint method was employed to interfere the bubble generated by underwater wet welding, and the new method was named as mechanical constraint assisted underwater wet welding. The aim of the study was to quantify the combined effect of wire feed speed and condition of mechanical constraint on the process stability in mechanical constraint assisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…These three types of electrodes caused the highest values of hardness in HAZ ( Section 3.3 ). Obtained results confirmed literature information [ 5 , 13 , 34 , 35 , 36 ], that high hardness increases the susceptibility of steel to cold cracking. The lowest number of parallel cracks in HAZ were observed in specimens welded by electrode with impregnate for concrete ( Figure 9 c).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…These three types of electrodes caused the highest values of hardness in HAZ ( Section 3.3 ). Obtained results confirmed literature information [ 5 , 13 , 34 , 35 , 36 ], that high hardness increases the susceptibility of steel to cold cracking. The lowest number of parallel cracks in HAZ were observed in specimens welded by electrode with impregnate for concrete ( Figure 9 c).…”
Section: Resultssupporting
confidence: 85%
“…The usage of paraffin wax caused hardness reducing by 20-40 HV10 in HAZ in comparison to electrode without additional hydrophobic layer and by 40-50 HV10 in comparison to underwater electrode. Expected hardness reducing in HAZ (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) was also observed in specimens welded with electrodes with concrete impregnate. The significant differences were found in the weld.…”
Section: Hardness Measurementsmentioning
confidence: 71%
See 1 more Smart Citation
“…This lowers the quality of the welded joints. Wang et al [ 14 ] stated that stability of the welding arc depends on the welding parameters. They found that lower welding current values increased the stability of the welding arc in wet welding conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great practical significance of problems associated with the storage of welding consumables, this topic is relatively rarely discussed in the literature. Previous works mainly concerned the impact of wire construction and storage conditions on the diffusible hydrogen amount in weld metal [ 18 , 22 , 38 ] and the influence of welding parameters and conditions on the quality and properties of welded joints [ 20 , 39 , 40 , 41 , 42 ]. Accordingly, the purpose of the work was to analyze the impact of storage conditions of seamless, copper plated flux-cored wires on the plasticity of the bead-on-plate welds made with these wires.…”
Section: Introductionmentioning
confidence: 99%